Zinc as a feed supplement and its impact on plasma cholesterol concentrations in breeding cocks - Parák, Tomáš (Acta veterinaria Brno, 2011)
The aim of this work was to verify the impact of feed supplemented with selected inorganic and organic zinc compounds on the total cholesterol concentrations and other blood plasma indices in breeding cocks. A total of 250 RIR 05 breeding cocks, 9 weeks old, were used. The cocks were divided into 5 groups of 50 animals each (four experimental groups and one control group). Cocks were fed a commercial feed mixture specifically for breeding cocks, containing 30.4 mg·kg-1 of zinc. The feed for experimental groups of cocks was fortified to 100 mg Zn·kg-1: zinc sulphate in first group, zinc oxide in second group, fodder yeast (Minvital Zn) in third group and Bioplex Zn in fourth group. Blood samples for biochemical examination were taken from the basilic vein. The contents of total cholesterol (Chol), total proteins (TP), glucose (Glu), aspartate aminotransferase (AST), alanine aminotransferase (ALT), calcium (Ca), phosphorus (P) and magnesium (Mg) in blood plasma were spectrophotometrically measured using a biochemical analyser, Cobas EMira, and commercial kits (Biovendor a.s., Czech Republic). In the 15th week of age, third and fourth groups showed a significant (P ≤ 0.05) and highly significant (P ≤ 0.01) decrease of total cholesterol in blood plasma compared to the control. In the 20th and 25th week of age, all of the experimental groups showed a significantand highly significant (P ≤ 0.01) decrease of total cholesterol in blood plasma compared to the control. Other monitored indices (total proteins, glucoses, aspartate aminotransferase, alanine aminotransferase, calcium, phosphorus and magnesium) did not reveal any significant changes between the experimental and the control groups. The presented work provides the first available experimental evidence regarding the impact of zinc supplementation on the cholesterol levels in blood plasma of breeding cocks.
Keywords: Animal Feed; krmivo pro zvířata; kur domácí; Cholesterol; Dietary Supplements; Animals; cholesterol; Zinc Compounds; mužské pohlaví; zvířata; Male; biologické markery; Chickens; Biomarkers; potravní doplňky; sloučeniny zinku